Membranas compostas de Alumina e Paládio para permeação de Hidrogênio - Terra, Natália Mazzarioli (2018)
The growing increase in demand for clean and renewable energy sources has fostered the interest in research for hydrogen (H2) production and purification. However, with the production of hydrogen there is usually the simultaneous generation of co-products. A viable alternative for obtaining high purity H2 is through palladium (Pd) based composite membranes, due to a remarkable solubility of H2 through these membranes which carry it dissociatively (allowing the permeation of H2 only) without formation of stable oxides on the surface of the membrane that reduce the permeation of hydrogen, as occurs in other metals. The main proposal of this study was to produce alumina hollow fiber supports with asymmetric pore distribution for deposition of Pd-based metallic membranes for hydrogen separation. Hollow fibers with different asymmetric structures were produced by varying the internal bore fluid (pure water, pure solvent dimethylsulfoxide (DMSO) and DMSO with ethanol). The hollow fibers produced with pure DMSO and DMSO with alcohol as internal bore fluid were named FO6 and FO8, respectively, and presented an internal micro-porous layer and a thin spongy-like layer ideal for Pd deposition. Hydrogen permeation was evaluated through composite membranes with different support structures and Pd thicknesses. For both FO8 and FO6 support, 3 cycles of 1 h of deposition (each) were required for the formation of a 100% selective membrane with thicknesses above 3.493 and 2.411 μm, and H2 fluxes of 0.033 and 0.096 mol s-1 m-2 at 450 °C and 100 kPa, for the supports FO8 and FO6, respectively. In order to reduce the roughness of the outer surface of the fiber FO6, polymer solutions of polyvinyl alcohol (PVA) and polyethersulfone (PES) were used, which reduced by 27.3 and 12.2%, respectively. However, the presence of the polymer generated defects in the palladium membrane, reducing significantly the selectivity (H2/N2) (< 4) to hydrogen. It was then chosen to cover the outer surface of the hollow fiber FO6 with graphite, which reduced the roughness by 36.1%, allowed the deposition of a layer of Pd of 1.807 μm, with a hydrogen flux of 0.102 mol s-1 m-2 at 450°C and 100 kPa and with infinite selectivity (H2/N2). To reduce the costs with the support, a fiber with thick alumina granulometry (approximately 4 μm) covered with fine alumina (1 μm) was produced. This coating was able to reduce in 62.2% the roughness of the outer surface of the fiber. With this fiber, a membrane with infinite selectivity was obtained with Pd thickness of 3.261 μm and H2 flux equal to 0.145 mol s-1 m-2 at 100 kPa and 450 °C. The deposition bath composition was changed and PdCl2 was used as a palladium source and using the support FO8 the MM08-1 membrane was produced with 1.049 μm thickness and H2 flux equal to 0.212 mol m-2 s-1 at 100 kPa and 450 °C. This membrane exhibited thermal stability for 120 h and infinite selectivity. Thus, the use of composite membranes formed by Pd layers deposited on a support of asymmetric alumina hollow fibers is a promising alternative for hydrogen separation since it is possible to achieve infinite selectivity at suitable hydrogen fluxes, compatible with the presented in the literature.